Expressividade poética à flor da tela: janelas para pensar três filmes latino-americanos - Silva, Edvânea Maria da (2015)
The films A teta assustada (2009), directed by Claudia Llosa, Whisky (2003), directed by Juan Pablo Rebella and Pablo Stoll and O segredo de seus olhos (2009), by Juan José Campanella, as any artistic text, exist ―only in the spirit which endows them with reality‖ (AUMONT, 1995, p. 225). The strategies adopted by each filmmaker have impregnated the narratives with poetical quality and opened a space for a politics of fiction. These narratives have functioned as windows which allowed us to think about the common human being; these were deliberate partial choices pregnant of an affective and a political perspective, whose aim was to under-stand the vicissitudes of our everyday life, through the stories of singular subjects/characters. Aiming to amplify the understanding of this issue, we carried out analyses of various fictional texts, through which we discussed the theoretical principles of poeticalness and metafiction, based on Jacques Rancière, Roman Jakobson, Linda Hutcheon, Patricia Waugh and texts by the Russian formalists. The objective of this research was therefore to investigate how Latin-American cinema, represented in three early films of the twenty-first century has proposed new ways of thinking about politics and subjectivity through a poetical action and vision.